Motivasi dan Lingkungan Kerja Untuk Meningkatkan Kinerja Karyawan Hotel - Sauma Fitriana; Ade Sobariah Hasanah; Rizal Sukma Aliyudin (Papanda Publisher, 2023)
Employee performance is an important factor in achieving company goals. Employee performance is one of the main factors that can affect organizational progress. The higher the performance of employees, the easier the goals of the organization will be achieved. Employee performance can be influenced by various factors, two of which are motivation and work environment. The purpose of this study was to determine the effect of motivation and work environment on employee performance at the Arya Kadipaten Hotel, Majalengka Regency. This study uses quantitative research methods with associative research types. The sample in this study was taken randomly as many as 16 respondents. The data collection technique used was to distribute questionnaires which were then processed using statistical analysis. The results showed that the work motivation of Hotel Arya employees was sufficient, as well as an increase in employee performance with increased employee motivation. The same results also show an increase in employee performance with an improved employee work environment. The results of multiple regression testing also show that motivation and work environment simultaneously affect employee performance. The conclusion of this study is that motivation and work environment can improve the performance of Hotel Arya Kadipaten employees.